2021
DOI: 10.3390/medicina57090897
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Strategies in Male Competitors of Combat Sport Disciplines

Abstract: Background and objective: The use of suboptimal weight loss strategies in order to reach specific weight ranges as observed in combat sport disciplines can give rise to severe health problems. However, particular aspects regarding management of weight category comparing three sport disciplines remain to be investigated. Therefore, the aim of the present study was to obtain information regarding the weight loss strategies that competitors performed before a tournament. Materials and Methods: This article descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Then the results of the pretest and posttest in the weight class showed that the higher weight class showed less results compared to the lower weight class. These results prove that body weight can affect athletes' movement and physiological abilities such as fitness [14,31]. However, in losing weight other factors must also be considered, especially the athlete's motivation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Then the results of the pretest and posttest in the weight class showed that the higher weight class showed less results compared to the lower weight class. These results prove that body weight can affect athletes' movement and physiological abilities such as fitness [14,31]. However, in losing weight other factors must also be considered, especially the athlete's motivation.…”
Section: Discussionmentioning
confidence: 69%
“…In general, body weight greatly influences the level of ability of martial arts athletes in the fighting category in demonstrating their technical and tactical skills. Based on research results in the sports of karate, judo and taekwondo, it shows that body weight affects mobility when fighting, whereas in judo it can affect the technique for slamming an opponent [14]. In addition, greater body weight greatly influences the level of damage received, as well as lighter body weight having an advantage in terms of agility [15].…”
Section: Introductionmentioning
confidence: 99%
“…Combat sports athletes have developed various strategies for weight cutting over the years, many of which have been researched. Common methods used by combat sports athletes include water loading, fluid restriction, dieting, increased exercise, sauna or hot bath, sauna suits, with rarer methods of spitting, laxatives, diuretics, diet pills, or vomiting [15,16,[22][23][24]37,46,47,[69][70][71][72][73]. While weight cutting practices have been shown to vary among combat sports [19,48], water loading, dieting, hot salt baths, and saunas were common strategies used among mixed martial arts athletes [12,16,21].…”
Section: Discussionmentioning
confidence: 99%
“…Athletes are weighed before the time between weighing and competition varying from less than 1 hour to 24 hours. To gain a weight advantage over an opponent, athletes will lose substantial weight over the days, weeks, and even months leading up to the weighing (Martínez-Rodríguez et al, 2021) & (Figlioli et al, 2021). In general, this activity has been carried out by many martial arts sports, but one example of martial arts that has been in the spotliregardingbout weight management is boxing.…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods that boxers use to lose weight such as the use of sauna jacket supplements, reducing the number of calories intake, for orsting several days (Kim & Park, 2020). Although there are several traditional methods of weight loss, namely by limiting carbohydrate intake that occurs and nando, karate, taekwondo sports (Martínez Rodríguez et al, 2021). Pencak silat, methods used include increasing exercise, skipping meals for 1 to 2 days, and using a sauna jacket (Teo et al, some consumeconsume who consume herbal supplements, namely spirulina for 12 days from martial wrestling (Nordvall et al, 2021).…”
Section: Introductionmentioning
confidence: 99%